Production Process Planning in Additive Manufacturing and Conventional Machining Technology Manufacturing System - Kellner, Tomas; Kyncl, Jiri; Pitrmuc, Zdenek; Beranek, Libor; Kanak, Michal; Kyncl, Martin (Manufacturing Technology Journal, 2019)
Main goal of this study is to describe and design manufacturing system which is using Additive manufacturing technology for production of semi-finished products and conventional machining technology for finishing operations, then demonstrate requirements of such production on simulation model on production planning and then analyze and summarize the outputs of the production model. The model is made with aid of modern Digital Factory tools. The main purpose of the model is to provide a complex tool for this study in order to analyze and optimize the fictive production system in needed range and complexity. The topic of Rapid Prototyping and Additive manufacturing technologies is very recent topic in industry. But still, there are only few examples of production systems, which are really using Rapid Prototyping technologies as a part of the production or production line. The advantage of these technologies is their versatility, but on the other hand, as a part of production system, they can have different demands on for example production planning, area consumption or maintenance, that can affect whole production system.
Keywords: Additive Manufacturing; Metal Printing and Machining; Digital Factory Tools; Production Optimization; Production Capacity Planning